Empowering Fish Farmers: Integrating Human Resource Capacity and Appropriate Aquaculture Innovation in Lumajang Regency - Nurman Riyadi; Siti Asiyah; Dwiyani Sudaryanti (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to analyze the effectiveness of fish farmer empowerment strategies implemented by the Fish Farmer Group (Pokdakan) in Lumajang Regency, with a focus on strengthening human resources (HR) and applying appropriate fish farming technology. The approach used is descriptive qualitative, with data collection techniques including interviews, participatory observation, and documentation. Informants include the Head of the Fisheries Department, fisheries extension officers, and active members of the Pokdakan. The research findings indicate that empowerment strategies through technical training, continuous mentoring, and the utilization of innovative technologies such as circular ponds, aerators, and probiotics have a positive impact on enhancing HR capacity, cost efficiency, and business productivity. The application of appropriate aquaculture techniques has also successfully promoted technical independence among farmers and strengthened the institutional framework of the group. Additionally, market access and social networks among members have expanded, indicating improved competitiveness of aquaculture businesses. In conclusion, the empowerment strategies implemented are effective and have the potential to serve as a model for other regions, although equitable access to training and financial support for all groups remains necessary. Recommendations are provided to ensure future empowerment programs are more inclusive and sustainable